Impact of sex differences on clinical characteristics of anti-N-methyl-D-aspartate receptor encephalitis during the acute phase: a single-center retrospective study - Zou, Xuan; Zhou, Guan-en (Frontiers in Human Neuroscience, 2026)
ObjectiveTo elucidate the influence of sex differences on the clinical characteristics of anti-NMDAR encephalitis during the acute phase.MethodsPatients diagnosed with anti-NMDAR encephalitis who were hospitalized at Huanhu Hospital, affiliated with Tianjin University, from January 2020 to January 2025 were collected. They were divided into two groups: male and female. Clinical data for both groups were gathered, including age, history of prodromal infection, clinical manifestations, complications, presence of tumor, laboratory indices, MRI findings, GCS scores, length of hospital stay, treatment regimens, and acute phase outcomes. Statistical methods were employed to compare the differences between the two groups.ResultsA total of 43 patients with anti-NMDAR encephalitis were included in this study, comprising 20 male patients (46.51%) and 23 female patients (53.49%). Female patients were more likely to exhibit decreased levels of consciousness compared to male patients (χ2 = 4.113, p = 0.043). Additionally, the antibody titers in CSF of female patients were significantly higher than those in male patients too (Z = −2.870, p = 0.004). Interestingly, CSF protein levels were higher in male patients than in female patients (Z = −2.591, p = 0.019), and male patients were more prone to test positive for anti-MOG antibodies (χ2 = 5.715, p = 0.017). The treatment improvement rate for female patients was lower than that for male patients (Z = 4.768, p = 0.029), and family members of female patients were more likely to automatic discharge (χ2 = 4.075, p = 0.044).ConclusionFemale patients with anti-NMDAR encephalitis experience greater challenges and difficulties compared to male patients. Therefore, it is necessary to choose more proactive treatment options for female patients to help reduce the risk of adverse outcome in acute phase.